Field evidence of riparian vegetation response to groundwater levels in a gravel‐bed river. Issue 2 (2nd February 2021) - Martinetti, Stefano; Fatichi, Simone; Floriancic, Marius; Burlando, Paolo; Molnar, Peter
Abstract: Vegetation establishment, growth and succession in riparian ecosystems are linked to river flow dynamics and groundwater table fluctuations. This is especially true in Alpine gravel‐bed rivers with wide floodplains, geomorphically active floods and a strong river‐aquifer exchange. The role of short‐term groundwater fluctuations is not always clear in these ecosystems, as it is assumed that phreatophytic vegetation close to rivers is adapted to such conditions. Here, we provide data evidence of riparian plant response to short‐term groundwater table fluctuations in a braided gravel‐bed river (Maggia). We used indirect physiological variables for photosynthesis and transpiration—stomatal conductance g s and daily variation in stem diameter Δ D d —which we measured at six mature riparian trees of the Salicaceae family at two sites with different mean depths to groundwater during two growing seasons. The data demonstrate that (a) short‐term variation of the groundwater table affects riparian vegetation—at the site with deeper groundwater, the water table depth was the best predictor of g s variability, while at the site with shallower groundwater, temperature and vapour pressure deficit ( V P D ) were the best predictors of Δ D d variability; (b) instantaneous stomatal conductance is related to V P D, but conditioned by groundwater levels, with higher stomatal conductance for the same radiative input and V P D when the water table was higher for all trees; and (c) local microclimate measured at tree locations had a stronger predictive power for g s than valley scale climate, suggesting local climate controls on vegetated stands on gravel bars. Our results provide evidence of riparian trees undertaking physiological adjustments to transpiration in response to groundwater stage, depending on their riparian floodplain setting.